Effect of Physical-Sports Leisure Activities on Young People’s Psychological Wellbeing - Rodríguez-Bravo, Ana Eva; De-Juanas, Ángel; García-Castilla, Francisco Javier (Frontiers in Psychology, 2020)
This article examines the impact of physical-sports activities on the psychological wellbeing of Spanish and Colombian young people. Scientific literature highlights that young people devote leisure time to sports for the purpose of enjoyment, and to maintain good health and body image. In addition, it provides the opportunity to socialize, and come into contact and connect with people who have shared interests. It is also an ideal resource for learning and developing social skills to ensure inclusion and the appropriate strategies for emotional management. Similarly, it favors the learning of values that promote the assumption of responsibilities, decision-making capacity, tolerance to frustration, and the development of resilience.This study considers the inherent benefits of physical-sports activities in order to analyze the impact on young people's assessment of their own psychological wellbeing.To this effect, a quantitative ex post facto study was designed, and Ryff's Model of Psychological Wellbeing was used with 1,148 young people from Spain and Colombia aged 16-21. The young people were asked whether or not they performed any type of physical-sports activity in their leisure time and the type of activity performed.The results show that young people who perform such activities have higher overall levels of psychological wellbeing. In turn, they emphasize that the perform of physical-sports activities has a positive impact on three of the dimensions of psychological wellbeing: self-acceptance, positive relations with others, and purpose in life. In addition, significant differences in young people's psychological wellbeing were found depending on whether they perform individual, team or other physical-sports activities.These results provide a basis for the proposal and design of interventions with young people based on sports and leisure activities as socio-educational strategies.